Lipopolysaccharide (LPS) down-regulates CD4 expression in primary human macrophages through induction of endogenous tumour necrosis factor (TNF) and IL-1 beta. - Herbein, G (1995)
The regulation of CD4 expression on macrophages and its role in immune cell interactions remain obscure. In contrast with primary lymphocytes, primary macrophages express only low amounts of surface CD4, which is regulated differentially for example by adherence in vitro. We report that addition of LPS for 1-5 days to human blood monocyte tissue culture-derived macrophages (TCDM) down-regulates both surface CD4 expression and total cellular CD4 antigen content as measured by flow cytometry and Western blot analysis. TNF-alpha and IL-1 beta, proinflammatory cytokines which are both induced by LPS, also down-regulate surface and total CD4 expression in TCDM. This down-regulation of CD4 expression by LPS, TNF-alpha, and IL-1 beta occurs at the level of transcription. The decreased macrophage CD4 expression induced by LPS was blocked by MoAbs directed against human TNF-alpha and IL-1 beta, demonstrating that LPS acts on CD4 expression through induction of endogenous TNF-alpha and IL-1 beta. Conversely, neither LPS nor TNF-alpha and IL-1 beta were able to modulate surface CD4 expression on quiescent or phytohaemagglutinin (PHA)-activated lymphocytes. Of other cytokines and growth factors tested, Th2 cytokines (IL-4, IL-10, IL-13), chemokines (MCP-1, MIP-1 alpha, RANTES), and macrophage colony-stimulating factor did not alter CD4 expression in primary macrophages; granulocyte-monocyte colony-stimulating factor and the prototypal Th1 cytokine interferon-gamma (IFN-gamma) modulated surface CD4 expression only after prolonged treatment (5 days). Our results show that LPS, TNF-alpha and IL-1 beta selectively down-regulate CD4 expression in primary human macrophages, and that decreased CD4 expression induced by LPS results from endogenous secretion of TNF-alpha and IL-1 beta by the macrophages.